The effect of the copper intrauterine device (Cu-IUD) and the injectable depo-medroxyprogesterone acetate (DMPA) use on women's sexual satisfaction and depression - Samaneh Hagh-Mohammadi Pasanad; Farnaz Farnam; Maryam Damghanian (Tehran University of Medical Sciences, 2020)
Background & Aim: Intrauterine device and depo-medroxyprogesterone acetate are among the most effective reversible contraception in the world, still few consensuses exist about sexual and mood changes of these two conventional methods. The present study has compared the sexual satisfaction and depression level in these two methods. Methods & Materials: A cross-sectional study was conducted between August 2017 and January 2018, in 300 married women aged 19-50 year, in Tehran, Iran. One hundred and fifty IUD users and 150 DMPA consumers, 12-18 months after starting the current method, recruited to the study from 34 health centers of Tehran University of Medical Sciences by convenience sampling. Two standard questionnaires of Index of sexual satisfaction (ISS) and Patient Health Questionnaire (PHQ) were used for assessing sexual satisfaction and depression, respectively. Chi-square and independent t-test were used for the homogeneity of the two groups. The linear logistic regression analysis was conducted to estimate the strength of associations. Results: There was not any significant difference between two groups in demographic characteristics such as age, marriage duration, education level, number of children and breastfeeding condition (P>0.05). Significantly higher sexual satisfaction (P<0.001) and lower depression level (P<0.001) reported in IUD users than DMPA consumers in the t-test. A multivariate regression confirmed that sexual satisfaction increased 6.4 scores in the IUD group in comparison to DMPA users (P= 0.003, B= -6.4), and with increase 1 year to duration of the marriage, sexual satisfaction increase 0.33 score. For depression, the only significant variable was the contraceptive methods, and depression level increase 1.24 scores in DMPA users than IUD consumers. (P=0.006, B= - 1.24). Although in univariate analysis, some variables showed effects on sexual satisfaction and depression, multivariate regression results did not confirm any significant relationships. Conclusion: Both sexual satisfaction and mood level was higher among IUD users. This paper reconfirmed that IUD is a preferable method in women who are eligible to use both methods.